2016
DOI: 10.1080/10888438.2015.1128435
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Movement Control in RAN and Reading

Abstract: The present study examined the visual scanning hypothesis, which suggests that fluent oculomotor control is an important component underlying the predictive relationship between Rapid Automatized Naming (RAN) tasks and reading ability. Our approach was to isolate components of saccadic planning, articulation, and lexical retrieval in three modified RAN tasks. We analyzed two samples of undergraduate readers (age 17–27), we evaluated the incremental contributions of these components and found that saccadic plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 72 publications
1
30
0
1
Order By: Relevance
“…For instance, some studies have supported the early results from Pavlidis showing eye movement differences in children with dyslexia and controls in non‐reading eye movement tasks. In contrast, other studies have shown no differences in eye movements during non‐reading tasks in individuals with dyslexia and poor readers compared to age‐matched controls. Hence, the relationship between saccades, fixations and reading performance remains unclear.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…For instance, some studies have supported the early results from Pavlidis showing eye movement differences in children with dyslexia and controls in non‐reading eye movement tasks. In contrast, other studies have shown no differences in eye movements during non‐reading tasks in individuals with dyslexia and poor readers compared to age‐matched controls. Hence, the relationship between saccades, fixations and reading performance remains unclear.…”
Section: Introductionmentioning
confidence: 67%
“…e.g. 18,19,48 In general, individuals with good/average reading skills make fewer fixations and regressions and also fixations are briefer than in poor readers. e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative explanations of the serial superiority effect invoking effects of executive function or visual scanning direction have failed to account for the observed associations (Altani, Protopapas, & Georgiou, 2017;Protopapas, Altani, & Georgiou, 2013b; but cf. Kuperman, van Dyke, & Henry, 2016).…”
Section: Differential Associations With Serial and Discrete Namingmentioning
confidence: 99%
“…Furthermore, children and adults diagnosed with a reading disorder are consistently reported to display less efficient patterns of eye movements during RAN and reading tasks, i.e., smaller perceptual spans, longer and more fixations per word, shorter saccades, and more regressions when compared with age-matched typical readers (Rayner, 1986;Ashby and Rayner, 2004;Jones et al, 2008;Logan, 2009;Hawelka et al, 2010;Jones et al, 2010;Moll and Jones, 2013;Pan et al, 2013;Yan et al, 2013;Al Dahhan et al, 2014Kuperman et al, 2016;Henry et al, 2018). Such differences in gaze patterns have been interpreted to reflect that those with reading difficulties require more attentional resources and time to attend and engage cognitive mechanisms in order to process information during fixations than normal age-matched readers.…”
Section: Introductionmentioning
confidence: 99%